The Effect of Community Socioeconomic Status on Sepsis-attributable Mortality - Galiatsatos, Panagis (J Crit Care, 2018)
PURPOSE: Community factors may play a role in determining individual risk for sepsis, as well as sepsis-related morbidity and mortality. We sought to define the relationship between community socioeconomic status and mortality due to sepsis in an urban locale. METHODS: Using community statistical areas of Baltimore City, we dichotomized neighborhoods at median household income, and compared distribution of outcomes of interest within the two income categories. We performed multivariable regression analyses to determine the relationship between socioeconomic variables and sepsis-attributable mortality. RESULTS: The collective median household income was $38,660 (IQR $32,530, 54,480), family poverty rate was 28.4% (IQR 13.5, 38.8%), and rate of death from sepsis was 3.1 per 10,000 persons (IQR 2.60, 4.10). Lower household income communities demonstrated higher rates of death from sepsis (3.65 (IQR 2.78, 4.40)) than higher household income communities (2.80 (IQR 2.05, 3.55)) (p=0.02). In regression models, household income (β= −8.42, p=0.006) and percentage of poverty in communities (β= 2.71, p=0.01) demonstrated associations with sepsis-attributable mortality. DISCUSSION: Our findings suggest that socioeconomic variables play significant role in sepsis-attributable mortality. Such confirmation of regional disparities in mortality due to sepsis warrants further consideration, as well as integration, for future national sepsis policies.